Soybean as Source of Functional Food - Ayda Krisnawati (Puslitbang Tanaman Pangan, 2017)
Soybean represents an excellent source of high quality protein with a low content of saturated fat and high in dietary fibre. The important of soybean as a functional food is reflected from the physiological content in its grain. The possible use of soybean as functional food in Indonesia is high, since the consumption of soybean and its processed products in the daily diet is stable high, that it seems to reduce the risk of cardiovascular disease. Soybean isoflavones are associated with roles in the prevention and treatment of degenerative organ diseases. The use of improved soybean variety as raw material for soy processed food showed similar quality with those of the imported ones. Therefore, research on the role of soybean as functional food has a strategic status in supporting the achievement of sustainable national food security.